Identification of Genetic Diversity of P21-Activated Kinases (PAK1) Gene in Senduro Goats and Boerawa Goats using PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) - Heri Damayanti; Susilorini, Tri Eko; Prasetyo, Guruh; Hidayah, Nur; Efendi, Ahmad Zarkasi; Ardiantoro, Ari; Septian, Wike Andre Septian; Suyadi, Suyadi (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aimed to detect genetic diversity associated with litter size traits of the P21-activated kinases (PAK1) gene in Senduro and Boerawa goats using the PCR-RFLP method. The restriction enzyme used is MSP1 (C*CGG). A pair of primers used in this study, namely Forward ((5'-GCTCAGTGTTGTATTAGCAG-3') and Reverse (5'- CAAGATATAAAGCACAGCCG-3') product length 713 bp (access code ENSCHIG00000003071). The samples used in this study consisted of 80 samples of Senduro goats and 20 samples of Boerawa goats from UPT PT-HMT Singosari, Malang Regency. The results showed that the PAK1 exon 9 gene in Senduro goats and Boerawa goats UPT PT-HMT Singosari was uniform (monomorphic), it was because all samples had GG genotype and G allele frequency of 100%. In conclusion, the PAK1 exon 9 / MSP1 gene is monomorphic and does not associate with litter size in Senduro goats and Boerawa goats, so it cannot be used as a genetic marker.